Comorbidity of headache and functional constipation in children: A cross-sectional survey - Inaloo, Soror; Dehghani, Seyyed Mohsen; Hashemi, Seyyed Mohammad; Heydari, Mojtaba; Heydari, Seyyed Taghi (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Constipation and headache are prevalent conditions among children worldwide. Previous studies have shown the relationship between upper gastrointestinal complaints and headache in children. However, the association with lower gastrointestinal complaints such as constipation has not been investigated until present. The aim of this study is to evaluate the relationship between headache and chronic functional constipation in children aged 4-12 years old. Materials and Methods: This cross-sectional study has evaluated the prevalence of headache in 326 children in Shiraz, Iran 2012. All the subjects and their parents were interviewed based on a structured questionnaire for the diagnosis of constipation and headache. Children with constipation were selected from the Pediatric Gastroenterology Clinic Affiliated to the Shiraz University of Medical Sciences. The control group was selected from healthy children attending Shiraz schools. Diagnosis of headache and constipation were made based on the second Edition of The International Headache Classification (ICHD-2) and ROME III criteria, respectively. Results: Headache prevalence among children with constipation was significantly higher (19.8%) than that of the control group (5.6%) [Odds ratio (OR) 4.192, p<0.001], which was significant only in the non-migraine headache subtypes (15.1% vs 2.8%, OR 25, p<0.002). Among the headache subtypes of different severity (mild, moderate, severe), only mild headache was significantly more prevalent in constipated children (14.9% vs. 1.4%, in the control group, respectively, p<0.001). Conclusion: This study revealed a strong correlation between headache and chronic functional constipation, which can result from the effect of these comorbid conditions with emotional stress, depression, and anxiety.